Robert Triffin. Vida internacional de las monedas. México : Centro de Estudios Monetarios Latinoamericanos, 1964. 161 p. - Buira, Ariel (El Colegio de México A.C., 1967)
ROBERT TRIFFIN. Vida internacional de las monedas. México, Centro de Estudios Monetarios Latinoamericanos, 1964.